2001
DOI: 10.1097/00001648-200109000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Do Pregnant Women Report Use of Dispensed Medications?

Abstract: Surveillance of drug safety in pregnancy often draws on administrative prescription registries. Noncompliance in the use of prescribed medication may be frequent among pregnant women owing to their fear of fetotoxic side effects. To estimate compliance in the use of prescription drugs dispensed during pregnancy, we compared prescription data from the North Jutland Prescription Database with information on drug use provided by pregnant women to the Danish National Birth Cohort (DNBC), which is a health intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
162
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(185 citation statements)
references
References 26 publications
12
162
6
Order By: Relevance
“…Compliance was high for drugs used in chronic diseases but low for drugs used for local or short-time treatment. 24 Furthermore, the prescription database does not include drugs administered in hospitals and OTC drugs. For some drugs, underestimation of exposure may be considerable.…”
mentioning
confidence: 99%
“…Compliance was high for drugs used in chronic diseases but low for drugs used for local or short-time treatment. 24 Furthermore, the prescription database does not include drugs administered in hospitals and OTC drugs. For some drugs, underestimation of exposure may be considerable.…”
mentioning
confidence: 99%
“…Although we recommend interpreting these results with caution, an association by timing of exposure cannot be dismissed completely. For comparison, a large US study reported that 0.8% of women received first trimester prescriptions for systemic corticosteroids (Andrade et al, 2004), with actual medication use probably less than 100% (Olesen et al, 2001). Furthermore, the prevalence is similar to what has been found in the National Health and Nutrition Examination Study (NHANES) during the years 1999 to 2008, where 0.5% of women aged 20 to 29 years and 0.6% of women aged 30 to 39 years reported use of oral corticosteroids (Overman et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Noncompliance with medication use may result in misclassification bias, where some of the women classified as 'exposed' were in fact not exposed during pregnancy. For example, Olesen and colleagues compared reporting of medication use during pregnancy among women enrolled in the Danish National Birth Cohort to the North Jutland prescription database, for those women living in the North Jutland area [Olesen et al 2001]. Medications used for chronic medical conditions (i.e.…”
Section: Assumptions Regarding Medication Usementioning
confidence: 99%